The Effects of Employee Stock Options on Credit Ratings - Lee, Yen-Jung (The Accounting Review, 2008)
ABSTRACT: This paper examines whether outstanding employee stock options (ESOs), which represent the firm’s contractual obligation to deliver shares upon ESO exercise, affect firms’ credit ratings. I hypothesize that outstanding ESOs play two information roles—(1) suggesting equity infusion, and (2) predicting share repurchases—that help credit-rating agencies evaluate the issuing company’s debt service ability. Consistent with these hypothesized roles, results indicate that the present values of expected cash proceeds and tax benefits from ESO exercise have favorable effects on credit ratings. In contrast, the present value of the expected cost of ESO-related share repurchases has an unfavorable effect on credit ratings and this unfavorable effect is more pronounced for firms with a greater tendency to repurchase shares. The after-tax fair value of outstanding ESOs, which summarizes the effects of the above three ESO-related cash flows, is negatively associated with credit ratings. Taken together, these findings are consistent with credit-rating agencies incorporating the information conveyed by outstanding ESOs regarding potential equity infusion and ESO-related repurchases in their credit risk assessments and assigning lower credit ratings to firms with greater values of outstanding ESOs.